Factors Related to Rabies Prevention Measures in Nangapanda Community Health Center, Ende, East Nusa Tenggara - Yuniarti Prihartini; Yendris K. Syamruth; Indriati A. Tedju Hinga (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Rabies is an acute infectious disease of the central nervous system caused by the rabies virus and transmitted through the bites of Rabies Transmitting Animals (HPR), especially dogs. The bite of an unvaccinated rabies-infecting animal is the cause of most cases of rabies which can lead to death. This study aimed to determine the factors related with the prevention of rabies in the community in the working area of the Nangapanda Community Health Center, Ende, East Nusa Tenggara. Subjects and Method: This cross-sectional study was conducted in the working area of the Nangapanda Public Health Center, Ende Regency from August to September, 2022. A total of 116 families were selected for this study. The dependent variable is rabies prevention measures and the independent variable is knowledge and attitude. Data were analyzed using the chi-square test. Results: Good knowledge (OR= 19.25; 95% CI= 5.94 to 62.36; p<0.001), and positive attitude (OR= 0.11; 95% CI= 0.02 to 0.53; p= 0.001) are associated with rabies prevention measures. Conclusion: There is a significant relationship between knowledge and attitude toward rabies disease prevention measures. Keywords: rabies, action, prevention. Correspondence: Yuniarti Prihartini. Study Program in Public Health, Faculty of Public Health, Universitas Nusa Cendana. Jl. Lasiana, Klp. Lima, Kupang, East Nusa Tenggara. Email: unny12835@gmail.com. Mobile: +62 821-8780-4312.